Chemical bridge-mediated heterojunction electron transport layers enable efficient and stable perovskite solar cells - Patil, Pramila; Maibam, Ashakiran; Sangale, Sushil S.; Mann, Dilpreet Singh; Lee, Hyun-Jung; Krishnamurty, Sailaja; Kwon, Sung-Nam; Na, Seok-In (ACS Applied Materials and Interfaces, 2023)
Perovskite solar cells (PSCs) emerged as potential photovoltaicenergy-generating devices developing in recent years because of theirexcellent photovoltaic properties and ease of processing. However,PSCs are still reporting efficiencies much lower than their theoreticallimits owing to various losses caused by the charge transport layerand the perovskite. In this regard, herein, an interface engineeringstrategy using functional molecules and chemical bridges was appliedto reduce the loss of the heterojunction electron transport layer.As a functional interface layer, ethylenediaminetetraacetic acid (EDTA)was introduced between PCBM and the ZnO layer, and as a result, EDTAsimultaneously formed chemical bonds with PCBM and ZnO to serve asa chemical bridge connecting the two. DFT and chemical analyses revealedthat EDTA can act as a chemical bridge between PCBM and ZnO, passivatedefect sites, and improve charge transfer. Optoelectrical analysisproved that EDTA chemical bridge-mediated charge transfer (CBM-CT)provides more efficient interfacial charge transport by reducing trap-assistedrecombination losses at ETL interfaces, thereby improving device performance.The PSC with EDTA chemical bridge-mediated heterojunction ETL exhibiteda high PCE of 21.21%, almost no hysteresis, and excellent stabilityto both air and light.
Keywords: charge transfer; chemical bridge; electron transport layer; ethylenediaminetetraacetic acid; Perovskite solar cells; trap-assisted recombination